Coating diaphragm with high heat resistance and high diaphragm rupture temperature as well as preparation method and application of coating diaphragm

By using porous substrates and heat -resistant coating in lithium battery septum, combined with polyolefins that combine high crystal and low melting indexes, the thermal performance problem of the diaphragm in high energy density and fast charging conditions has been solved, and the battery has significantly improved the battery. Safety performance.

CN119340615APending Publication Date: 2025-01-21WUHAN ZHONGXING INNOVATIVE MATERIAL TECHNOLOGIES CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411355771.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing lithium battery separators are prone to rupture or heat shrinkage due to heat accumulation under high energy density and fast charging conditions, resulting in short circuits within the battery and affecting safety performance.

Method used

The porous substrate is used as the basis of the diaphragm. The surface of the surface is coated with heat-resistant coating. The middle layer uses a crystallinity of 40%-60%, the regulation of the equalization ≥90%, and the melting index ≤ 0.5g/10min Layers use a crystallinity of 20%-60%, equal regulations ≥85%, and the melting index of 0.1g/10min-2.0g/10min polylefin B, and add a polymer with a hydrogen bonding group to the surface layer.

Benefits of technology

It improves the heat resistance and membrane rupture temperature of the separator, reduces the thermal shrinkage rate, enhances the safety performance of the battery, and reduces the risk of short circuit.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340615A_ABST
    Figure CN119340615A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of battery diaphragms, in particular to a high-heat-resistance and high-diaphragm-rupture-temperature coating diaphragm and a preparation method and application thereof.The coating diaphragm comprises a porous base material and heat-resistant coatings arranged on the two surfaces of the porous base material; the porous base material comprises a middle layer and surface layers arranged on the two sides of the middle layer, the middle layer comprises polyolefin A, the surface layers comprise polyolefin B, and the polyolefin A meets the requirements that the crystallinity is 40%-60%, the isotacticity is larger than or equal to 90%, and the melt index is smaller than or equal to 0.5 g / 10 min. The middle layer has relatively high melt strength, so that the diaphragm has a relatively low thermal shrinkage rate, can bear self gravity or certain external acting force at high temperature, maintains the integrity of the diaphragm material, and can improve the diaphragm rupture temperature and safety performance of the diaphragm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of battery separators, and more specifically to a coating separator with high heat resistance and high membrane rupture temperature, and a preparation method and application thereof. Background Art

[0002] Ion batteries have the characteristics of high energy density, good safety, and long cycle life. They are widely used in power, energy storage, 3C and other fields. They have been commercialized and maturely applied, and have become an indispensable product in people's daily life, work, and commercial activities. Among them, the safety performance of lithium batteries is one of the basic performances that all kinds of consumer groups pay the most attention to. The diaphragm in the lithium battery system has the function of isolating the positive and negative electrodes and conducting ions, which can effectively prevent the occurrence of unsafe factors such as lithium battery short circuit. With the emergence of high-energy-density fast-charging batteries, high energy density will be accompanied by the problem of insufficient heat release, resulting in heat accumulation at the diaphragm, causing the diaphragm to break or shrink, thereby causing a short circuit inside the battery.

[0003] Therefore, how to improve the heat resistance and membrane rupture temperature of the diaphragm is a technical problem that needs to be solved urgently in the development of the battery industry. Summary of the invention

[0004] The present application provides a highly heat-resistant and high-breakdown-temperature coated diaphragm and a preparation method and application thereof, which has good heat resistance and high breakdown temperature and can improve the safety performance of the diaphragm and the battery.

[0005] The present application provides a coating diaphragm with high heat resistance and high membrane rupture temperature, comprising a porous substrate and a heat-resistant coating disposed on both surfaces of the porous substrate, the porous substrate comprising an intermediate layer and surface layers disposed on both sides of the intermediate layer, the intermediate layer comprising polyolefin A, and the surface layer comprising polyolefin B;

[0006] The polyolefin A satisfies the requirements of crystallinity of 40%-60%, isotacticity ≥90%, and melt index ≤0.5g / 10min.

[0007] In an optional embodiment, the melt index of the polyolefin A is less than or equal to the melt index of the polyolefin B;

[0008] Optionally, the polyolefin B satisfies a crystallinity of 20%-60%, an isotacticity of ≥85%, and a melt index of 0.1 g / 10 min-2.0 g / 10 min.

[0009] In an optional embodiment, the surface layer further comprises a polymer having hydrogen bonding groups;

[0010] Optionally, in the surface layer, the mass percentage of the polyolefin B is 60%-90%, and the mass percentage of the polymer is 10%-40%.

[0011] In an optional embodiment, the sum of the thicknesses of the two surface layers accounts for 20%-60% of the total thickness of the porous substrate.

[0012] In an optional embodiment, the total thickness of the porous substrate is 10 μm-30 μm.

[0013] In an optional embodiment, the polymer includes at least one of ethylene-vinyl alcohol copolymer, propylene-propylene alcohol copolymer, polyvinyl pyrrolidone, polyethylene glycol, polyvinyl alcohol, polyurethane, polyacrylamide and polyvinylidene fluoride.

[0014] In an optional embodiment, the heat-resistant coating satisfies at least one of the conditions (1)-(2):

[0015] (1) The heat-resistant coating comprises one or more of ceramic, aramid, polyimide, and cellulose;

[0016] (2) The thickness of the heat-resistant coating is 2 μm-10 μm.

[0017] The present application provides a method for preparing a coating diaphragm with high heat resistance and high film breaking temperature, comprising:

[0018] The middle layer raw material and the surface layer raw material are respectively added into two extruders for melting;

[0019] The melted intermediate layer raw material and the surface layer raw material are co-extruded synchronously from a three-cavity three-layer composite casting die head, and cooled and pulled to obtain a three-layer co-extruded casting film;

[0020] Annealing the three-layer co-extruded cast film, and then sequentially stretching and heat-setting the film after annealing to obtain the porous substrate;

[0021] Prepare heat-resistant coatings on both surfaces of the porous substrate to obtain the coated diaphragm;

[0022] The raw material of the intermediate layer includes polyolefin A; the raw material of the surface layer includes polyolefin B; the polyolefin A satisfies the requirements of crystallinity of 40%-60%, isotacticity ≥90%, and melt index ≤0.5g / 10min.

[0023] In an optional embodiment, the method for preparing the diaphragm satisfies at least one of the conditions (1)-(6):

[0024] (1) When the three-layer composite casting die is co-extruded, the extrusion temperature of the middle layer is 200° C.-250° C., and the extrusion temperature of the surface layer is 200° C.-300° C.;

[0025] (2) When the three-layer co-extruded cast film is obtained by cooling and pulling, the cooling temperature is 80° C.-100° C.;

[0026] (3) The annealing temperature during the annealing treatment is 130° C.-160° C.;

[0027] (4) The stretching includes hot drawing and cold drawing, the temperature of the hot drawing is 130°C-160°C, and the ratio of the hot drawing is 1.5-2.5; the temperature of the cold drawing is 80°C-100°C, and the ratio of the cold drawing is 1.0-1.5;

[0028] (5) The heat setting temperature is 150°C-170°C;

[0029] (6) The surface layer raw material also includes a polymer having hydrogen bonding groups; the preparation method of the surface layer raw material includes the following steps: mixing the polymer having hydrogen bonding groups and the polyolefin B according to a ratio and modifying the polypropylene B to obtain the surface layer raw material.

[0030] The present application provides a lithium-ion battery, comprising the above-mentioned high-heat-resistant and high-breakdown-temperature coated diaphragm, or a diaphragm prepared by the above-mentioned method for preparing the above-mentioned high-heat-resistant and high-breakdown-temperature coated diaphragm.

[0031] The high heat-resistant and high film-breaking temperature coating diaphragm according to the above-mentioned embodiment comprises a porous substrate and a heat-resistant coating disposed on both surfaces of the porous substrate, the porous substrate comprises an intermediate layer and surface layers disposed on both sides of the intermediate layer, the intermediate layer comprises polyolefin A, and the surface layer comprises polyolefin B. The heat-resistant coating is disposed on the surface of the porous substrate, so that the diaphragm has high heat resistance, and can make the diaphragm size change small at ultra-high temperature, and the force is small, so that the diaphragm has a low thermal shrinkage rate; the intermediate layer uses a polyolefin with a low melt index, so that the intermediate layer has a relatively high melt strength, and can bear its own gravity or a certain external force at high temperature to maintain the integrity of the diaphragm, so that the diaphragm has a high film-breaking temperature, which can comprehensively improve the film-breaking temperature and safety performance of the diaphragm. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 It is a schematic diagram of the structure of a coating diaphragm with high heat resistance and high film rupture temperature in an embodiment.

[0033] Wherein: 100, porous substrate; 110, surface layer; 120, middle layer; 200, heat-resistant coating. DETAILED DESCRIPTION

[0034] The present application is further described in detail below by specific embodiments in conjunction with the accompanying drawings. Wherein similar elements in different embodiments adopt associated similar element numbers. In the following embodiments, many detailed descriptions are intended to enable the present application to be better understood. However, those skilled in the art can easily recognize that some of the features can be omitted in different situations, or can be replaced by other elements, materials, and methods. In some cases, some operations related to the present application are not shown or described in the specification, in order to avoid the core part of the present application being overwhelmed by too much description, and for those skilled in the art, it is not necessary to describe these related operations in detail, and they can fully understand the related operations based on the description in the specification and the general technical knowledge in the art.

[0035] In addition, the features, operations or characteristics described in the specification can be combined in any appropriate manner to form various implementations, and the operation steps involved in each embodiment can also be replaced or adjusted in a sequence in a manner that is obvious to those skilled in the art. Therefore, the specification and drawings are only for the purpose of clearly describing a certain embodiment and do not mean that the composition and / or sequence are necessary.

[0036] The serial numbers of the components in this document, such as "first", "second", etc., are only used to distinguish the objects described and do not have any order or technical meaning. The "connection" and "coupling" mentioned in this application, unless otherwise specified, include direct and indirect connections (couplings).

[0037] Secondary batteries refer to batteries that can be used again by recharging the active materials after the battery is discharged. This type of battery usually uses the reversibility of chemical reactions, that is, after a chemical reaction is converted into electrical energy, the chemical system can be repaired with electrical energy, and then converted into electrical energy by chemical reaction again. Among them, the more common secondary batteries include but are not limited to nickel-metal hydride batteries, nickel-cadmium batteries, lead-acid (or lead storage) batteries, lithium-ion batteries, polymer lithium-ion batteries, sodium-ion batteries, etc.

[0038] In this application, the so-called "diaphragm" is an important component of the secondary battery cell. The diaphragm is a thin film used to separate the positive and negative electrodes during the electrolysis reaction to prevent the loss of energy in the direct reaction. The performance of the diaphragm determines the interface structure and internal resistance of the battery, and directly affects the battery's capacity, cycle and safety performance. A diaphragm with excellent performance plays an important role in improving the overall performance of the battery.

[0039] MD (Machine Direction) is the machine direction, that is, the longitudinal direction, and TD (Transverse Direction) is perpendicular to the machine direction, that is, the transverse direction.

[0040] See also Figure 1 The present application discloses a high heat-resistant and high-breakdown-temperature coating diaphragm for lithium-ion batteries, comprising a porous substrate 100 and a heat-resistant coating 200 disposed on both surfaces of the porous substrate 100. The porous substrate 100 is a three-layer structure, comprising an intermediate layer 120 and surface layers 110 disposed on both sides of the intermediate layer 120. The intermediate layer 120 comprises polyolefin A, that is, the intermediate layer 120 is a porous structure mainly formed by polyolefin A, and the surface layer 110 comprises polyolefin B. Since the heat-resistant coating 200 is disposed on the surface of the porous substrate 100, the diaphragm has high heat resistance, can make the diaphragm size change small at ultra-high temperature, and can bear small force, so that the diaphragm has a low thermal shrinkage rate, which can improve the safety performance of the diaphragm.

[0041] In an optional embodiment, polyolefin A satisfies a crystallinity of 40%-60%, an isotacticity ≥ 90%, and a melt index ≤ 0.5g / 10min, that is, the middle layer 120 uses a polyolefin with a relatively high crystallinity and a relatively low melt index. For example, the crystallinity of the polyolefin used in the middle layer 120 can be 40%, 45%, 50%, 55% or 60%, the isotacticity can be 90%, 91%, 92%, 95%, 96%, 97% or 100%, and the melt index can be 0.05g / 10min, 0.1g / 10min, 0.2g / 10min, 0.3g / 10min, 0.4g / 10min or 0.5g / 10min. Polypropylene with high crystallinity and low melt index has high melt strength, can bear its own gravity or a certain external force at high temperature, maintain the integrity of the diaphragm, and thus can increase the diaphragm breaking temperature.

[0042] In an optional embodiment, the melt index of polyolefin A is less than or equal to the melt index of polyolefin B, that is, the middle layer 120 uses a polyolefin with a lower melt index, and the surface layer 110 uses a polyolefin with a relatively higher melt index, so that the middle layer 120 has a relatively high melt strength, and can bear its own gravity or a certain external force at high temperature to maintain the integrity of the diaphragm, so that the diaphragm has a lower thermal shrinkage rate and can also increase the rupture temperature of the diaphragm. The surface layer 110 has better processing performance and lower hardness, and can play a role in buffering external forces.

[0043] In an optional embodiment, polyolefin B satisfies a crystallinity of 20%-60%, an isotacticity of ≥85%, and a melt index of 0.1g / 10min-2.0g / 10min. For example, the crystallinity of the polyolefin of the surface layer 110 can be 20%, 25%, 30%, 35% or 40%, the isotacticity can be 85%, 86%, 88%, 89%, 90%, 91% or 92%, and the melt index can be 0.1g / 10min, 0.2g / 10min, 0.3g / 10min, 0.4g / 10min, 0.5g / 10min, 0.8g / 10min, 1.0g / 10min, 1.5g / 10min or 2.0g / 10min. Preferably, polyolefin B satisfies a crystallinity of 20%-40%, an isotacticity of ≥85%, and a melt index of 1.0g / 10min-2.0g / 10min. The melt index of the surface layer 110 is within the above range, and its processing performance is good. After being prepared as the surface layer, it has the characteristic of low hardness. If it is subjected to external forces such as extrusion and friction during the process, the surface layer can reduce the damage to the surface layer by elastic deformation, stress relaxation, etc. due to its own low hardness, thereby reducing the occurrence of weak points in the diaphragm, improving the overall pressure resistance of the battery diaphragm, and reducing the risk of short circuit in the battery.

[0044] In an optional embodiment, the surface layer 110 also includes a polymer having a hydrogen bonding group, that is, the surface layer 110 is a porous structure mainly formed by a polyolefin B modified by a polymer having a hydrogen bonding group. Since the surface layer 110 of the porous substrate 100 uses a polyolefin B modified by a polymer having a hydrogen bonding group, the wettability of the surface of the porous substrate 100 can be improved, the uniformity of the coating of the heat-resistant coating 200 on the surface of the porous substrate 100 can be improved, the stability and reliability of the connection with the heat-resistant coating 200 can be improved, and the liquid absorption rate of the diaphragm can also be improved.

[0045] In an optional embodiment, in the surface layer 110, the mass percentage of polyolefin B is 60%-90%, for example, the mass percentage of polyolefin B can be 60%, 65%, 70%, 80%, 85% or 90%. The mass percentage of the polymer is 10%-40%, for example, the mass percentage of the polymer can be 10%, 15%, 20%, 30%, 35% or 40%.

[0046] In an optional embodiment, the sum of the thicknesses of the two surface layers 110 accounts for 20%-60% of the total thickness of the porous substrate 100. For example, the sum of the thicknesses of the two surface layers 110 accounts for 20%, 30%, 40%, 50% or 60% of the total thickness of the porous substrate 100. When the percentage of the sum of the thicknesses of the surface layers 110 to the total thickness of the porous substrate 100 is controlled within the above range, the separator has relatively ideal comprehensive properties.

[0047] In an optional embodiment, in the porous substrate 100, the total thickness of the intermediate layer 120 and the two surface layers 110 is 10 μm-30 μm, that is, the thickness of the porous substrate 100 is 10 μm-30 μm, for example, the thickness of the porous substrate 100 can be 10 μm, 12 μm, 15 μm, 20 μm, 25 μm, 28 μm or 30 μm.

[0048] In an optional embodiment, the polymer includes at least one of ethylene-vinyl alcohol copolymer, propylene-propylene alcohol copolymer, polyvinyl pyrrolidone, polyethylene glycol, polyvinyl alcohol, polyurethane, polyacrylamide and polyvinylidene fluoride.

[0049] In an alternative embodiment, the polyolefin includes polypropylene.

[0050] In an optional embodiment, the heat-resistant coating 200 includes one or more of ceramic, aramid, polyimide, and cellulose. The above materials have good high heat resistance, and the use of them to prepare the heat-resistant coating 200 has a significant effect on improving the heat resistance of the diaphragm. In some embodiments, ceramics and adhesives can be used to prepare the heat-resistant coating slurry.

[0051] In an optional embodiment, the thickness of the heat-resistant coating 200 is 2 μm-10 μm. For example, the thickness of the heat-resistant coating 200 may be 2 μm, 4 μm, 6 μm, 8 μm, 9 μm or 10 μm.

[0052] The present application also provides a method for preparing a coating diaphragm with high heat resistance and high film breaking temperature, wherein the raw materials for preparing a porous substrate 100 are co-extruded and cooled by a co-extrusion process to obtain a three-layer structure of an intermediate layer 120 and two surface layers 110 attached to both sides of the intermediate layer 120, and the steps specifically include:

[0053] The raw materials of the middle layer 120 and the raw materials of the surface layer 110 are respectively added into two extruders for melting;

[0054] The molten raw material of the middle layer 120 and the raw material of the surface layer 110 are co-extruded from a three-cavity three-layer composite casting die head simultaneously, and cooled and pulled to obtain a three-layer co-extruded casting film, wherein the raw material of the middle layer 120 includes polyolefin A; the raw material of the surface layer 110 includes polyolefin B, and the polyolefin A meets the requirements of crystallinity of 40%-60%, isotacticity ≥90%, and melt index ≤0.5g / 10min;

[0055] The three-layer co-extruded cast film is subjected to annealing treatment, and then stretched and heat-set in sequence after annealing to obtain a porous substrate 100;

[0056] The heat-resistant coating layer 200 is formed on both surfaces of the porous substrate 100 to obtain a coated separator.

[0057] In an optional embodiment, based on the different melt indexes of the polyolefins of the middle layer 120 and the surface layer 110, the extrusion temperatures of the two are also different. Since the melt index of the middle layer 120 is less than or equal to the melt index of the surface layer 110, when co-extruding and melting, the extrusion temperature of the middle layer 120 is lower than the extrusion temperature of the surface layer 110. Specifically, when the three-layer composite casting die is co-extruded, the extrusion temperature of the middle layer 120 is 200°C-250°C, and the extrusion temperature of the surface layer 110 is 200°C-300°C. For example, the extrusion temperature of the middle layer 120 can be 200°C, 210°C, 220°C, 230°C, 240°C or 250°C, and the extrusion temperature of the surface layer 110 can be 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, 290°C or 300°C.

[0058] In an optional embodiment, when cooling and pulling to obtain a three-layer co-extruded cast film, the cooling temperature is 80°C-100°C, for example, the cooling temperature can be 80°C, 85°C, 90°C, 95°C, 98°C or 100°C.

[0059] In an optional embodiment, the annealing temperature during the annealing treatment is 130°C-160°C, for example, the annealing temperature may be 130°C, 140°C, 150°C or 160°C.

[0060] In an optional embodiment, the stretching includes hot drawing and cold drawing, the temperature of the hot drawing is 130°C-160°C, and the ratio of the hot drawing is 1.5-2.5, for example, the temperature of the hot drawing can be 130°C, 140°C, 150°C or 160°C, and the ratio of the hot drawing can be 1.5, 1.6, 1.8, 2.0, 2.1, 2.3 or 2.5. The temperature of the cold drawing is 80°C-100°C, and the ratio of the cold drawing is 1.0-1.5, for example, the temperature of the cold drawing can be 80°C, 85°C, 90°C, 95°C, 98°C or 100°C, and the ratio of the cold drawing can be 1.0, 1.1, 1.2, 1.3, 1.4 or 1.5.

[0061] In an optional embodiment, the heat setting temperature is 150° C.-170° C. For example, the heat setting temperature may be 150° C., 155° C., 160° C., 165° C. or 170° C.

[0062] The present application also provides an application of a coating diaphragm with high heat resistance and high membrane rupture temperature, which can be specifically applied in lithium-ion batteries to improve the safety performance of lithium-ion batteries.

[0063] The present application also provides a lithium-ion battery, comprising the above-mentioned high heat-resistant and high-breakdown-temperature coating diaphragm. Specifically, the coating diaphragm is arranged between the positive electrode and the negative electrode of the lithium-ion battery to isolate the positive electrode from the negative electrode.

[0064] The technical solution of the present application is further described below through specific embodiments.

[0065] Embodiment 1

[0066] Prepare polypropylene resin particles with an isotacticity of 96%, a crystallinity of 56%, and a melt index of 0.1 g / 10 min as polyolefin A for preparing the intermediate layer 120; prepare polypropylene resin particles with an isotacticity of 86%, a crystallinity of 20%, and a melt index of 2.0 g / 10 min as polyolefin B for preparing the surface layer 110; prepare propylene-propylene alcohol high molecular copolymer as polymer C. The polyolefin B and the polymer C are blended in a mass ratio of 4:1 to prepare a blend D, the blend D and the polyolefin A are added into a coextrusion device, and a prefabricated film of a D / A / D structure is formed by coextrusion (wherein the D layer is extruded from the blend D, and the A layer is extruded from the polyolefin A); wherein the extrusion processing temperature of the D layer is 260°C, and the extrusion processing temperature of the A layer is 230°C; the prefabricated film is cooled by a casting roller at 85°C to form a cast film, and then wound up for 2500m, and then annealed at 143°C for 15h; and then longitudinally stretched, wherein the cold drawing temperature is 85°C, the stretching ratio is 1.3, the hot drawing temperature is 153°C, and the stretching ratio is 2.1; after the stretching is completed, heat setting is performed at 163°C. Finally, a porous substrate 100 with a thickness of 12 μm and a porosity of 39% is prepared. The porous substrate 100 includes an intermediate layer 120 made of polyolefin A, and a surface layer 110 located on the upper and lower surfaces of the intermediate layer 120 and made of blend D, wherein the surface layer 110 accounts for 30% of the total thickness of the porous substrate 100.

[0067] Embodiment 2

[0068] The difference between the second embodiment and the first embodiment is that the polyolefin A of the selected intermediate layer 120 has an isotacticity of 92%, a crystallinity of 40%, and a melt index of 0.5 g / 10 min.

[0069] Embodiment 3

[0070] The difference between the third embodiment and the first embodiment is that the polyolefin A of the selected intermediate layer 120 has an isotacticity of 92%, a crystallinity of 40%, and a melt index of 0.3 g / 10 min.

[0071] Embodiment 4

[0072] The difference between the fourth embodiment and the first embodiment is that the mass ratio of the polyolefin B and the polymer C in the surface layer 110 is 9:1.

[0073] Embodiment 5

[0074] The difference between the fifth embodiment and the first embodiment is that the mass ratio of the polyolefin B and the polymer C in the surface layer 110 is 3:2.

[0075] Embodiment 6

[0076] The difference between Example 6 and Example 1 is that the polyolefin B selected for the surface layer 110 has an isotacticity of 90%, a crystallinity of 36%, and a melt index of 0.5 g / 10 min.

[0077] Embodiment 7

[0078] The difference between the seventh embodiment and the first embodiment is that the mass ratio of the surface layer 110 to the total thickness of the porous substrate 100 is 20%.

[0079] Embodiment 8

[0080] The difference between the eighth embodiment and the first embodiment is that the mass ratio of the surface layer 110 to the total thickness of the porous substrate 100 is 60%.

[0081] Embodiment 9

[0082] The difference between the ninth embodiment and the first embodiment is that the polyolefin B used to prepare the surface layer 110 is replaced with the polyolefin A used to prepare the middle layer 120 , that is, the same polyolefin A is used for the surface layer 110 and the middle layer 120 of the porous substrate 100 .

[0083] Embodiment 10

[0084] The difference between the tenth embodiment and the first embodiment is that the surface layer 110 is directly prepared by using polyolefin B, that is, the content of polymer C in the surface layer 110 is 0.

[0085] Comparative Example 1

[0086] The difference from Example 10 is that the isotacticity of polyolefin A is 86%, the crystallinity is 20%, and the melt index is 2.0 g / 10 min.

[0087] The compositions of the porous substrate 100 of Examples 1 to 10 and Comparative Example 1 can be found in Table 1.

[0088] Table 1

[0089]

[0090]

[0091]

[0092] The porous substrate 100 of the above-mentioned embodiments and comparative examples was tested. The testing method is as follows:

[0093] Thickness test: refer to GB / T 6672-2001, use a handheld thickness gauge to measure, take 5 points every 5cm along the TD direction of the membrane, the average value is the total thickness of the diaphragm, the thickness unit is μm. Functional layer 200 thickness = total diaphragm thickness - substrate layer 100 thickness.

[0094] Permeability test: The permeability is measured by EG01-55-1MR permeability meter and is expressed as the time taken for 100 mL of gas to pass through a fixed area diaphragm;

[0095] Heat shrinkage test: The test method is carried out in accordance with GB / T 12027-2004. Take 5 samples of 100mm×100mm or larger along the MD and TD directions of the sample, and measure the size before heating. The sample is sandwiched between A4 papers and put into the oven. After the set time is reached, such as heating at 150℃ for 1h, take it out and measure the size after heating. Calculate the heat shrinkage according to the formula.

[0096] Film rupture temperature test: refer to GB / T36363-2018 standard, use a hot stage microscope to test the film rupture temperature of the sample, record the temperature of the sample when it starts to melt, test each group of samples three times, and calculate the average value.

[0097] Contact angle test: drop the electrolyte onto the sample surface, and after 1 minute, use a video contact meter to test the contact angle between the sample and the electrolyte, repeat 5 times and take the average value. The electrolyte is composed of lithium hexafluorophosphate (LiPF6), ethylene carbonate (EC), and propylene carbonate (PC), where EC and PC are solvents, with a mass ratio of 1:1, and the concentration of LiPF6 in the electrolyte is 1 mol / L.

[0098] Liquid creeping length test: drop 5μL of electrolyte onto the surface of a diaphragm with a specification of 5mm*100mm and measure the electrolyte diffusion length for 20s. The diffusion length is taken as the liquid creeping length value. The liquid creeping length of the unmodified diaphragm is about 0.35cm.

[0099] The test results are shown in Table 2 below.

[0100] Table 2

[0101]

[0102] It can be seen from the data in Table 2 that, by comparing Example 1, Example 2 and Example 3, it can be seen that the lower the melt index of the middle layer 120 of the porous substrate 100, the higher the strength of the porous substrate 100 at high temperature, and the better the film breaking temperature and thermal dimensional stability; by comparing Example 1, Example 4, Example 5 and Example 10, it can be seen that the higher the hydrogen bond content in the surface layer 110 of the porous substrate 100, the better the wetting effect of the electrolyte on the porous substrate 100, the longer the creeping liquid length of the porous substrate 100 and the smaller the contact angle; by comparing the data of Example 1, Example 6 and Example 9, it can be seen that the melt index of the surface layer 110 material of the porous substrate 100 is low, and the material melt is strong. The degree of melt index is high, which can improve the film breaking temperature and thermal dimensional stability of the porous substrate 100 at high temperature; compared with Example 7, Example 1 and Example 8, as the content of the intermediate layer 120 with high melt index and low melt strength in the porous substrate 100 decreases, the film breaking temperature of the porous substrate 100 decreases and the thermal stability becomes worse; compared with Comparative Example 1, Examples 1 to 10 have a high film breaking temperature. When the polyolefin raw material used has high crystallinity, high isotacticity and low melt index, the polymer melt strength is relatively high. Under high temperature conditions, the high melt strength diaphragm can withstand its own weight while also being able to withstand the action of external forces to maintain the integrity of the diaphragm. The resulting diaphragm has a high film breaking temperature and better thermal dimensional stability.

[0103] A heat-resistant coating 200 was coated on the porous substrate 100 prepared in the above-mentioned Examples 1 to 10 and Comparative Example 1 to obtain a diaphragm, and the performance of the diaphragm was tested. The test results are shown in Table 3 below.

[0104] The preparation method of the heat-resistant coating 200 includes:

[0105] Slurry preparation: Al 2 O 3 (D50 = 300 nm), polyacrylamide, dispersant, wetting agent and deionized water are mixed in a mass ratio of 20:4.5:0.1:0.1:75.3, and stirred evenly to obtain a coating slurry;

[0106] Slurry coating: Take the porous substrate 100 prepared in the above Examples 1 to 10 and Comparative Example 1, roll-coat the above coating slurry on both sides of the porous substrate 100, and then dry at 80°C to remove moisture to obtain a battery separator A with a porous heat-resistant coating 200.

[0107] Comparative Example 2

[0108] A comparative battery separator B is prepared as a comparative example of the comparative battery separator A. The preparation method of the comparative battery separator includes:

[0109] Slurry preparation: Al 2 O 3(D50=300nm), polyacrylamide, dispersant, wetting agent and deionized water are mixed in a mass ratio of 20:4.5:0.1:0.1:75.3, and stirred evenly to obtain a coating slurry.

[0110] Slurry coating: Take the porous substrate 100 prepared in the above Example 1, roll-coat the above coating slurry on one side of the porous substrate 100, and then dry it at 80°C to remove moisture, so as to obtain a battery separator B with a porous heat-resistant coating 200.

[0111] Table 3

[0112]

[0113]

[0114] Comparing the above-mentioned battery separator A and battery separator B, it is found that the heat-resistant coating 200 can reduce the thermal shrinkage rate of the separator under high temperature, and the double-sided coating of the heat-resistant coating 200 can well protect the porous substrate 100 so that the film rupture temperature and heat resistance of the entire coating separator are better; the introduction of hydrogen bonds in the surface layer 110 of the porous substrate 100 can enhance the bonding strength between the heat-resistant coating 200 and the porous substrate 100, so that the porous substrate 100 can be well protected by the heat-resistant coating 200, and the heat resistance and film rupture temperature of the separator can be improved; the hydrogen bonds of the surface layer 110, the high melt strength and low melt index of the middle layer 120, and the surface heat-resistant coating 200 can effectively increase the film rupture temperature of the separator and reduce the thermal shrinkage of the separator.

[0115] The above specific examples are used to illustrate the present application, which is only used to help understand the present application and is not intended to limit the present application. For technicians in the technical field to which the present application belongs, they can also make some simple deductions, deformations or substitutions based on the ideas of the present application.

Claims

1. A coating diaphragm with high heat resistance and high film breaking temperature, characterized in that: It comprises a porous substrate and a heat-resistant coating disposed on two surfaces of the porous substrate, wherein the porous substrate comprises an intermediate layer and surface layers disposed on both sides of the intermediate layer, the intermediate layer comprises polyolefin A, and the surface layer comprises polyolefin B; The polyolefin A satisfies the following requirements: crystallinity of 40% to 60%, isotacticity of ≥ 90%, and melt index of ≤ 0.5 g / 10 min.

2. The high heat-resistant and high film-breaking temperature coating diaphragm according to claim 1, characterized in that: The melt index of the polyolefin A is less than or equal to the melt index of the polyolefin B; Optionally, the polyolefin B satisfies a crystallinity of 20%-60%, an isotacticity ≥85%, and a melt index of 0.1 g / 10 min-2.0 g / 10 min.

3. The high heat-resistant and high film-breaking temperature coating diaphragm according to claim 1 or 2, characterized in that: The surface layer also includes a polymer having hydrogen bonding groups; Optionally, in the surface layer, the mass percentage of the polyolefin B is 60%-90%, and the mass percentage of the polymer is 10%-40%.

4. The high heat-resistant and high film-breaking temperature coating diaphragm according to claim 1 or 2, characterized in that: The sum of the thicknesses of the two surface layers accounts for 20%-60% of the total thickness of the porous substrate.

5. The high heat-resistant and high film-breaking temperature coating diaphragm according to claim 1 or 2, characterized in that: The total thickness of the porous substrate is 10 μm-30 μm.

6. The high heat-resistant and high film-breaking temperature coating diaphragm according to claim 3, characterized in that: The polymer includes at least one of ethylene-vinyl alcohol copolymer, propylene-propylene alcohol copolymer, polyvinyl pyrrolidone, polyethylene glycol, polyvinyl alcohol, polyurethane, polyacrylamide and polyvinylidene fluoride.

7. The high heat-resistant and high film-breaking temperature coating diaphragm according to claim 1, characterized in that: The heat-resistant coating satisfies at least one of the conditions (1)-(2): (1) The heat-resistant coating comprises one or more of ceramic, aramid, polyimide, and cellulose; (2) The thickness of the heat-resistant coating is 2 μm-10 μm.

8. The method for preparing a coating diaphragm with high heat resistance and high film breaking temperature according to any one of claims 1 to 7, characterized in that: include: The middle layer raw material and the surface layer raw material are respectively added into two extruders for melting; The melted intermediate layer raw material and the surface layer raw material are co-extruded synchronously from a three-cavity three-layer composite casting die head, and cooled and pulled to obtain a three-layer co-extruded casting film; Annealing the three-layer co-extruded cast film, and then sequentially stretching and heat-setting the film after annealing to obtain the porous substrate; Prepare heat-resistant coatings on both surfaces of the porous substrate to obtain the coated diaphragm; The raw material of the intermediate layer includes polyolefin A; the raw material of the surface layer includes polyolefin B; the polyolefin A satisfies the requirements of crystallinity of 40%-60%, isotacticity ≥90%, and melt index ≤0.5g / 10min.

9. The method for preparing a coating diaphragm with high heat resistance and high film breaking temperature according to claim 8, characterized in that: The method for preparing the diaphragm satisfies at least one of the conditions (1) to (6): (1) When the three-layer composite casting die is co-extruded, the extrusion temperature of the middle layer is 200° C.-250° C., and the extrusion temperature of the surface layer is 200° C.-300° C.; (2) When the three-layer co-extruded cast film is obtained by cooling and pulling, the cooling temperature is 80° C.-100° C.; (3) The annealing temperature during the annealing treatment is 130° C.-160° C.; (4) The stretching includes hot drawing and cold drawing, the temperature of the hot drawing is 130°C-160°C, and the ratio of the hot drawing is 1.5-2.5; the temperature of the cold drawing is 80°C-100°C, and the ratio of the cold drawing is 1.0-1.5; (5) The heat setting temperature is 150°C-170°C; (6) The surface layer raw material also includes a polymer having hydrogen bonding groups; the preparation method of the surface layer raw material includes the following steps: mixing the polymer having hydrogen bonding groups and the polyolefin B according to a ratio and modifying the polypropylene B to obtain the surface layer raw material.

10. A lithium ion battery, characterized in that: A diaphragm comprising the high heat-resistant and high film-breaking temperature coating diaphragm as described in any one of claims 1 to 7, or a diaphragm prepared by the method for preparing the high heat-resistant and high film-breaking temperature coating diaphragm as described in claim 8 or 9.